Potassium Deficiency Significantly Affected Plant Growth and Development as Well as microRNA-Mediated Mechanism in Wheat (Triticum aestivum L.) - Zhang, Baohong; Thornburg, Thomas E.; Liu, Jia; Xue, Huiyun; Fontana, Julia E.; Wang, Guo; Li, Qian; Davis, Kyle E.; Zhang, Zhiyong; Liu, Mingjiu; Pan, Xiaoping (Frontiers in Plant Science, 2020)
It is well studied that potassium deficiency induced aberrant growth and development of plant and altered the expression of protein-coding genes. However, not too much systematical investigation on root development affected by potassium deficiency and no report on miRNA expression during potassium deficiency in wheat. In this study, we found that potassium deficiency significantly affected wheat seedling growth and development, evidenced by reduced plant biomass and small plant size. In wheat cultivar AK-48, up-ground shoots were more sensitive to potassium deficiency than roots. Potassium deficiency did not affect root vitality but do affected root development, including root branching, root area, and root size. Potassium deficiency delayed seminal root emergence but enhanced seminal root elongation, total root length and correspondingly total root surface area. Potassium deficiency also affected root and leaf respiration at the early exposed stage, but these affects was not observed as treatment going. One mechanism causing potassium deficiency impact is microRNAs (miRNAs), one important class of small regulatory RNAs. Potassium deficiency induced the aberrant expression of miRNAs and their targets, which further affected plant growth and development as well as response to abiotic stress, including nutrient deficiency. Thus, this positive root adapts to potassium deficiency could be caused by miRNAs associated with root development.